Boundaries and Boundary Objects: An Evaluation Framework for Mixed Methods Research. (July 2019) - Wenger-Trayner, Beverly; Wenger-Trayner, Etienne; Cameron, Josh; Eryigit-Madzwamuse, Suna; Hart, Angie
While mixed methods research is increasingly established as a methodological approach, researchers still struggle with boundaries arising from commitments to different methods and paradigms, and from attention to social justice. Combining two lines of work—social learning theory and the Imagine Program at the University of Brighton—we present an evaluation framework that was used to integrate the perspectives of multiple stakeholders in the program's social interventions. We explore how this "value-creation framework" acts as a boundary object across "boundaries of practice, " specifically across quantitative and qualitative methods, philosophical paradigms, and participant perspectives. We argue that the framework's focus on cycles of value creation provided the Imagine Program with a shared language for negotiating interpretation and action across those boundaries.